Investigating the association between dietary patterns and male reproductive health: a meta-analysis - Nguyen, Thanh Tung; Tran, Thi Thanh Mai; Truong, Thi Phuong Lan (Tạp chí Y Dược Huế, 2024)
Background: Male reproductive health has experienced a substantial global decline. This meta-analysis was conducted to investigate the influence of different dietary patterns on male reproductive function based on semen parameters, sperm DNA fragmentation, and sex hormones. Methods: The effects of dietary patterns on male reproductive health were examined by conducting a literature search of the PubMed, Science Direct, Google Scholar, and Web of Science databases using relevant keywords. The data extracted from the studies were analyzed using Random-Effects Models in STATA software, and the standard mean difference (SMD) was used to compare the groups with high and low intakes of each dietary pattern. Publication bias was assessed using Egger’s test. Results: The meta-analysis revealed a significant difference between healthy and unhealthy diets in terms of total sperm count, with the former showing a higher count (SMD, 0.30; 95% CI, -0.53 to 1.12). However, no significant differences were observed between healthy and unhealthy diet patterns in other semen parameters such as semen volume, sperm concentration, progressive motility, total motility, normal morphology, abnormal morphology, sperm defects, and DNA fragmentation index. This study indicated that healthy dietary patterns had a positive effect on enhancing SHBG levels (SMD, 1.48; 95% CI, 0.25 to 2.71). Additionally, the data showed that eating patterns did not significantly affect Testosterone, Estradiol, FSH, and Inhibin B levels. Conclusion: The relationship between dietary patterns and male reproductive function is complex, with food intake directly affecting both the total sperm count and sex hormone-binding globulin levels. This scientific evidence serves as a foundation for future research on diets that promote male fertility